(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The environment in which humans, as well as all animals, live, including natural phenomena, including volcanoes, earthquakes, celestial bodies, storms, hurricanes, lightning strikes, droughts, as well as changes in human life and pollution